Measurements of branching fractions, polarizations, and direct CP-violation asymmetries in B+→ρ0K*+ and B+→f0(980)K*+ decays - Amo Sanchez, Pablo del; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We present measurements of the branching fractions, longitudinal polarization, and direct CP-violation asymmetries for the decays B+→ρ0K*+ and B+→f0(980)K*+ with a sample of (467±5)×106B¯¯¯B pairs collected with the BABAR detector at the PEP-II asymmetric-energy e+e− collider at the SLAC National Accelerator Laboratory. We observe B+→ρ0K*+ with a significance of 5.3σ and measure the branching fraction B(B+→ρ0K*+)=(4.6±1.0±0.4)×10−6, the longitudinal polarization fL=0.78±0.12±0.03, and the CP-violation asymmetry ACP=0.31±0.13±0.03. We observe B+→f0(980)K*+ and measure the branching fraction B(B+→f0(980)K*+)×B(f0(980)→π+π−)=(4.2±0.6±0.3)×10−6 and the CP-violation asymmetry ACP=−0.15±0.12±0.03. The first uncertainty quoted is statistical and the second is systematic.